Utilização de um robô manipulador móvel para regulagem automática de gotejadores em irrigação localizada - Castro, Josué Pereira de (2024)
In localized irrigation, drippers are used for water and nutrient application, allowing for a more rational use of these resources. However, the use of drippers is subject to blockages caused by various factors, which can be of physical, chemical, or even biological nature, necessitating periodic maintenance. This maintenance consists of manually adjusting the emitters and must be done precisely. Considering the irrigated area in question, this process may not be practical. An alternative is to use active valves, but these are generally high-cost. In this context, robotics emerges as an alternative to reduce costs and facilitate the task of adjusting the emitters. In this project, a low-cost prototype of a teleoperated/autonomous mobile manipulator robot was used to automatically adjust the drippers. It is equipped with a mobile base with omnidirectional wheels, coupled with an articulated arm to adjust the emitters. The embedded software enables it to move to locate the emitters and perform the necessary adjustments. In the experiments conducted, a test platform shaped like an L with 20 distributed drippers was used, and the robot was operated in teleoperated mode; the experiment was conducted in two cycles: (a) monito ring and (b) adjustment. In (a), readings of all drippers were taken, and the collected data were processed using control charts for each dripper to identify flows outside the specified range. In (b), adjustments were made only to the drippers that exhibited flows greater or less than the specified limits, aiming to keep all drippers permanently within the specified limits. As a result, flow control of all drippers was achieved, increasing uniformity, calculated by the three indices (CUC, CUD, CUE), while keeping the flow within the system-imposed limits, thus improving the efficiency of the irrigation system mounted on the test platform. The conclusions drawn from the experiment were: (a) the robot was capable of collecting and adjusting the drippers in teleoperated mode; (b) the control charts were effective in identifying deviations in the operation of the drippers; (c) analyses conducted on the uniformity indices show that the system continu ously evolves, improving its uniformity regardless of the adopted index, as the system executes.